Modern Strategies of Learning in the Educational Process - Akhmedova, Matluba Akmalovna (European Journal of Life Safety and Stability (2660-9630), 2022)
The article deals with modern strategies for learning in an educational procession, which includes conclusions from the analysis of the socio-educational situation, the goals of education, the principles for selecting and designing the content of education, a view of the student as a participant in the educational process, as well as the relationship between these components of the system.